Feeding body and soul: Finnish missionaries and famine relief in German South West Africa at the beginning of the 20th century - Essi Huuhka (My University, 2025)
This article discusses the secular and religious meaning of the relief work by Finnish Christian missionaries in Ovamboland in the former South West Africa at the beginning of the twentieth century. Ovamboland regularly suffered crop failures and food scarcity, therefore, famine relief became an established part of the missionaries’ everyday work. This article discloses the concrete policies of distributing relief as well as the divine significance the missionaries attached to the hunger catastrophes. Even though the religious conviction was usually the most important signifier when the missionaries categorise the local people, famine relief was provided for both the baptized and unbaptized Ovambos. The missionaries also understood famines as good opportunities to gather people into the mission stations and preach the Christian gospel to them. Thus, they distributed both bodily food and spiritual food to the people.